Die Stabilisierungswirkungen von Mindestreserven - Ulrich Bindseil (Deutsche Bundesbank, 1997)
This paper focuses on the quest ion whether reserve requirements can contribute anything to the stabilization of financial markets and economic activity ...
Keywords: 330; Mindestreserve; Geldmarkt; Zins; Effizienzmarkthypothese; Volatilität; Geldtheorie; Informationsökonomik; Theorie